Application of remote sensing and GIS for mapping changes in land area and mangrove density in the Kuri Caddi Mangrove tourism, South Sulawesi Province, Indonesia - DWI ROSALINA; HAWATI HAWATI; KATARINA HESTY ROMBE; AGUS SURACHMAT; AWALUDDIN AWALUDDIN; MUCHTAR AMILUDDIN; ANI LEILANI; ASRIYANTI ASRIYANTI (Society for Indonesian Biodiversity, 2023)
Abstract. Rosalina D, Hawati, Rombe KH, Surachmat A, Awaluddin, Amiluddin M, Leilani A, Asriyanti. 2023. Application of remote sensing and GIS for mapping changes in land area and mangrove density in the Kuri Caddi Mangrove tourism, South Sulawesi Province, Indonesia. Biodiversitas 24: 1049-1056. One element of the coastal ecosystem crucial to preserving aquatic production and sustaining coastal dwellers' way of life is the mangrove. Several variables, including temperature, salinity, pH, natural disasters, and human activity, can affect mangrove forests and create changes. In the Kuri Caddi Mangrove ecotourism, Maros Regency, South Sulawesi, mangrove density was calculated, and changes in land area were mapped. From October to November 2022, this study was carried out. The Shapefile (SHP) format was used in the GIS (Geographic Information System) program to calculate changes in the area of mangrove land, and the NDVI (Normalized Difference Vegetation Index) method was employed to calculate density. The Kuri Caddi Mangrove Tourism, Marusu Sub-district, Maros Regency, mangrove forest land area increased by about 0.7 Ha between 2014 and 2017, according to an analysis of changes in the area there. From 2017 to 2021, significant changes were indicated by adding 4.05 Ha of land. Supporting environmental conditions and other aspects relating to human activity cause changes in land area. Because mangroves are still growing after rehabilitation, the NDVI values for 2014 and 2017 show a negligible increase in density. However, changes in the NDVI value will start to climb in 2021. The highest NDVI values will be 0.593, 0.652, and 0.691 in 2014, 2017, and 2021, respectively.